AB1177 A cohort of patients with antisynthetase syndrome evaluated in a multidisciplinary consultation. (12th June 2018) - Tornero, C.; Nuño, L.; Bonilla, G.; Gomez-Carrera, L.; Álvarez-Sala, R.; Balsa, A.
Abstract : Background: Antisynthetase syndrome (AS) is an uncommon connective tissue disease characterised by the presence of antibodies to anti-aminoacyl t-RNA synthetase (anti-ARS) along with features of interstitial lung disease (ILD), myositis, arthritis and Mecanic's hands. Objectives: To analyse the most common demographic, clinical, radiological, spirometry and capillaroscopic findings in a cohort of patients with AS. As a secondary objective, the association between capillaroscopic findings and diffusion lung capacity for carbon monoxide (DLCO) and the radiologic pattern in the high-resolution computed tomography of the chest (HRCT) was evaluated. Methods: A ten-year (2007–2017) retrospective analysis of patients diagnosed with AS followed in a multidisciplinary consultation with a pulmonologist and a rheumatologist. The nailfolds from 2nd to 5th fingers in both hands were examined in all subjects by using videocapillaroscopy (Mediscope-Optilia). Results: Twenty patients were included, 15 (75%) females and 50% (10/20) non-smokers. Mean age at the clinical debut was 47, 5±16 years. Throughout their evolution, 90% of patients (18/20) presented Interstitial Lund Disease (ILD); 70% (14/20), arthritis and 75% (15/20), myositis. Furthermore, 40% (8/20) associated fever, 45%; (9/20), Raynaud's Phenomenon and 55% (11/20), Mechanic's hands. Three patients only had ILD and Raynaud's Phenomenon at presentation. In the immunologic assessment, 73, 7% (14/19) were positive for anti – Jo-1 antibodies and 26, 3%, for anti PL-12. As non-anti-ARS antibodies, 6 had positivity for rheumatoid factor; 3, for ACPA and 5, for antiRo-52 antibodies. Of those 18 diagnosed of ILD, spirometry tests at baseline were available for 13. It was remarkable that 69, 23% (9/13) of patients presented a diminished value of DLCO (low in 23% (3/13), moderate in 46% (6/13) and normal in the rest of subjects. The most common ILD pattern was non-specific interstitial pneumonia (55%, 10/18 ) followed by usual interstitial pneumonia ( 33, 3%, 6/18) and organising pneumonia ( 11, 1%, 2/18). Nailfold capillaroscopy was performed in 16 patients: Scleroderma pattern was observed in 5 (all of them associating Raynaud's phenomenon) and 6 patients showed microangiopathic changes. The most frequent capillaroscopic findings were neoangiogenesis (93, 8%) and microhaemorragias 68, 8 followed by avascular areas (37, 5%) and megacapillaries (31%). An association between capillaroscopic findings and reduction of DLCO or the radiologic pattern was not observed, possibly influenced by the number of patients included. One subject associated Sjögren Syndrome, another one cutaneous Lupus and another patient, morphea. All of the patients included, received steroids and inmunosupressants. Azathioprine was the most frequently used (18/20), followed by Methotrexate (7/20), Rituximab (5/20), Mycophenolate (4/20), Cyclophosphamide (3/20) and Abatacept (1/20). Conclusions: In our cohort with AS, the most common clinical manifestation was ILD, and an important part of the patients showed a decreased DLCO. Capillaroscopy was pathogenic in most of them and could be useful for the diagnosis of AS, specially in those patients presenting solely with ILD at the clinical debut, although its pronostic value is still unknown. Multidisciplinary consultations are useful in the management of these truly challenging patients. Disclosure of Interest: None declared